Significados en torno a la indemnización y la restitución en víctimas del conflicto armado en el municipio de San Carlos (2016)
The results of the inquiries on the valuation that the very victims make of the armed conflict, in the Municipality of San Carlos, Antioquia, Colombia of the implementation of the 1448 Law (Law of victims); such a process of research, made evident among other findings, the contradiction between the official discourse and the story of the victims in relation to the processes of repair, contradictory speeches regarding the transition, the state of infringement and dissatisfaction of victimized people’s basic needs, as well as a high confusion in the implementation of the Law. These findings, among others, allow to affirm that, repair today, is very far from being a process that contributes to the reconstruction of the social fabric, to peace, and reconciliation.